Compressive Strength of Concrete Containing Merapi Cold Lava Sand - Bungalolon, Theo Trichius Cilvin Peden; Bali, Ika (PRESUNIVE CIVIL ENGINEERING JOURNAL, 2024)
Reports from the literature state that Merapi sand is a good material as a filler in concrete to replace some of the fine aggregate because it has a high content of silica (SiO2) and the sharp edges of the silica form angular particles. The potential function of Merapi sand as a filler and its use as a waste material prompted this study to be carried out. The objective of this study is to determine the potential of Merapi Sand in terms of concrete compressive strength as an effective replacement for local sand in the Cikarang area. In this study, Merapi cold lava was crushed to the size of fine aggregate by passing a 2.26 mm sieve. The percentages of Merapi sand used as a partial substitute for local sand are 10%, 20%, and 30%. The results of this study show that Merapi sand concrete (MSC) 30% at age of 7 days and 28 days provides the highest increase in compressive strength of 17.4% and 15.8% respectively compared to normal concrete (NC). The addition of a percentage of Merapi sand as a partial replacement for local sand tends to increase the compressive strength of the concrete. Based on this study, Merapi sand has the potential to be used as a partial replacement for local sand in increasing the compressive strength of concrete and reducing cold lava waste.